Clinical Benefit to an Aurora A Kinase Inhibitor in a Patient with Metastatic Integrase Interactor 1‐Deficient Carcinoma. (8th October 2018) - Karantanos, Theodoros; Rooper, Lisa; Kang, Youme; Lin, Cheng Ting; Wenga, Pawla; Sagorsky, Sarah; Lauring, Josh; Kang, Hyunseok
Abstract: : Integrase interactor 1 (INI‐1)‐deficient carcinoma is a rare cancer characterized by the loss of the SWItch/Sucrose Non‐Fermentable‐related matrix‐associated actin‐dependent regulator of chromatin subfamily B member 1 gene ( SMARCB1 ) and tends to follow an aggressive clinical course. There is no currently available standard therapy option, although a few promising treatment strategies, including enhancer of zeste homolog 2 (EZH2) inhibition, are under active investigation. This report describes a 30‐year‐old woman with INI‐1‐deficient carcinoma who progressed on combination chemotherapy and an EZH2 inhibitor. Next‐generation‐sequencing‐based targeted cancer‐related gene assay confirmed SMARCB1 loss and revealed other mutations in breast cancer 1 gene and checkpoint kinase 2 gene, which may have impacted her clinical course. After discussion at the molecular tumor board, she was offered alisertib, an aurora A kinase inhibitor, on a single‐patient expanded‐use program and achieved prolonged disease stabilization. Aurora A kinase inhibition may have an important role in the management of patients with INI‐1‐deficient tumors, warranting further evaluation in clinical studies. Key Points: Loss of the SWItch/Sucrose Non‐Fermentable‐related matrix‐associated actin‐dependent regulator of chromatin subfamily B member 1 gene ( SMARCB1 ), which encodes integrase interactor 1 (INI‐1), is associated with various mesenchymal malignancies, but a few carcinomas with rhabdoid features have been recently described as a distinct entity. INI‐1‐deficient carcinoma can be very aggressive, and there is no known treatment option available. There are encouraging preliminary data with an enhancer of zeste homolog 2 inhibitor, tazematostat, in INI‐1‐deficient malignancies, including INI‐1‐deficient carcinomas. Loss of INI‐1 can activate aurora A kinase (AurkA), and inhibition of AurkA by alisertib could be a viable option and warrants further investigation in this cancer. Clinical genomic profiling can confirm diagnosis of molecularly defined malignancy and provide insights on therapeutic options. Abstract : INI‐1 deficient carcinoma is characterized by loss of the SMARCB1 gene. Standard treatments options are currently unavailable for this rare and aggressive cancer. This report describes the case of a patient with INI‐1 deficient carcinoma and the course of treatment resulting in disease stabilization.